“Vida loka até o fim” ou não: as porosidades no Centro de Reintegração Social Feminino de Foz do Iguaçu - Simões, Katiuska Glória (2017)
The present dissertation exposes the results of the research realized in the Center of Female Social Reintegration in the city of Foz do Iguaçu (CRESF). The general objective of the reseach was discuss the prison institution and it's porosity, using as exemple the language of the internal, that is, the use and the non use of different forms of comunication, action where we can observe the relation that each internal has with the prison institution and between them. It was possible to observe a relation between the use and non use of certain forms of comunication among the internals and how they stand front of the institutionalization. The importance of this work is evidenced, considering the statistical data. Currently, Brasil has six times the amount of imprisoned of the end of 80's decade, owning the fifth largest female imprisoned population. The research was produced from the bibliographical revision about the theme, analysis of disponibilized data by the administration of the prison ant the realization of direct observation in CRESF for approximately one year. With the research was possible to evidence that the total institution, concept defended by Erving Goffman, presents porosity in the case fo the referenced female prison. In this sense, affirms that doesn't have a mortification of the "me" in a homogeneous way that reach all the internals. The use or non-use of the language elaborated by the internals reveals the diversity existent and the relation that each internal has with the institution, how some consider the prison a place or a non-place.